Off-axis Holographic Interferometer with Ensemble Deep Learning for Biological Tissues Identification - H. H.S. Lam; Yanmin Zhu; Prathan Buranasiri (Research Square, 2022)
Abstract This paper proposes a method with an off-axis interferometer and an ensemble deep learning (I-EDL) hologram-classifier to interpret noisy digital holograms captured from the tissues of flawed biological specimens. The holograms are captured by an interferometer which serves as a digital holographic scanner to scan the tissue with 3D information. A red laser beam penetrates the tissue of the specimen. It scans across the x-y directions to capture thousands of off-axis hologram samples for the training, testing, and recognizing the microstructure of the tissue and, hence, identifying the specimens' identity. The method achieves a high success rate of 99.60% in identifying the specimens through the tissue holograms. It is found that the ensemble deep learning hologram-classifier can effectively adapt to optical aberration coming from dust on mirrors and optical lenses aberration such as the Airy-plaque-like rings out-turn from the lenses in the interferometer. The deep learning network effectively adapts to these irregularities during the training stage and performs well in the later recognition stage without prior optical background compensations. The method does not require an intact sample with a full outline shape of the specimens or the organs to understand the objects' identities. It demonstrates a new paradigm in object identification by ensemble deep learning through a direct wavefront recognition technique.
Keywords: Digital Holography and Microscopy; Optical measurement and interference techniques; Advanced Optical Imaging Technologies